Numerical Thermal Comfort Analysis Using Combined Computer-Simulated Person with Clothing and Multi-Node Thermoregulation Model - Hyun-Gyu Park; Sung-Jun Yoo; Eisaku Sumiyoshi; Hiroshi Harashima; Ito Kazuhide (E3S Web of Conferences, 2023)
To analyse the interaction between the indoor environment and the human body, various computer-simulated persons (CSP) which can treat specific characteristics of the human body have been suggested as a “digital twin” for experimental thermal manikin. However, previous studies simplified or ignored the reproduction of the clothing function. In this study, a digital twin based on ANDI thermal manikin integrated with a multi-node thermoregulation model was developed in a naked and clothed state. In addition, to validate the prediction accuracy of numerical thermoregulatory analysis coupled with CSPCFD simulation, the analysis results were compared with the experimental results using thermal manikin. The computational model was generated based on 3D scan data of ANDI manikin and clothe. Moreover, the user subroutine program for coupled simulation of CSP and Fiala thermoregulation model was developed and applied into CSP to estimate the heat generation by metabolism, heat transfer between layers and parts, and skin surface temperature. CFD analysis was performed using CSP under identical environmental condition with the experiment, by setting CFD boundary conditions based on the data measured in the experiment. Through a series of numerical analyses, we confirmed that the analysis result of CSP corresponds well with experimental results using thermal manikin.